Evaluating the Impact of the DECIDE Model on Decision-Making Skills in Elementary Teacher Education Students in Indonesia - Salimi, Moh; Hidayah, Ratna; Suhartono; Susiani, Tri Saptuti; Wahyono; Wahyudi, Achmad Basari Eko; Fajari, Laksmi Evasufi Widi (Universitas Pendidikan Ganesha, 2024)
The low level of decision-making skills among students poses a significant challenge in elementary teacher education programs. This study aims to evaluate decision-making skills using the DECIDE model among elementary teacher education students in Indonesia. The research employed a qualitative method with a case study design. The participants consisted of 70 students selected through purposive sampling. Data were collected using open-ended essay tests and non-test techniques, including participant observation and in-depth interviews. The results indicated that students' decision-making skills could be evaluated through the six stages of the DECIDE model: Define the Problem, demonstrated by the ability to define the problem and identify the main aspects requiring resolution; Establish the Criteria, reflected in the ability to establish relevant and objective criteria for evaluating potential solutions; Consider all the Alternatives, shown by the ability to assess all alternatives along with their advantages and disadvantages; Identify the Best Alternative, characterized by the ability to identify the best alternative based on the established criteria; Develop and Implement a Plan of Action, shown through the development of a structured action plan; and Evaluate and Monitor the Solution, demonstrated by continuous evaluation of the implemented solution. This study concluded that elementary teacher education students in Indonesia exhibit good decision-making skills based on the DECIDE model.